Discrete mathematics and its applications with combinatorics and graph theory - Rosen, Kenneth H. (New Delhi: Tata McGraw-Hill Education Private Limited, 2007)
The book gives a lot of stress on mathematical reasoning, combinatorial analysis, algorithmic thinking, and applications and modeling. One of the most popular book in use, it gives a presentation of the subject in great depth. The text is strengthened with a host of pedagogical tools which help in making it student friendly. New to this edition Language used is easy to understand. Comprehensive coverage of Induction, Recursion, and Counting. Algorithms in the text are given using pseudocodes. Applications included, demonstrate the utility of the subject in terms of Real-World problems. Pedagogical Features: 2992 Exercise Problems 195 Review Questions 480 Supplementary Exercises 152 Computer Projects 93 Computations & Explorations 140 Writing Projects New to the Edition: A separate chapter on Discrete Structures (Chapter 2) The new chapter 4 on Induction and Recursion. Conditional Statements & De Morgan's Laws receive expanded coverage. Material on Valid Arguments and Rules of Inference is presented in a separate section. Coverage of Turing Machines expanded. Over 400 new exercises and several new examples have been added. The introduction of Basic Counting Techniques, and Permutations and Combinations enhanced.
Bibliography B1-B9p.; Index I1-I23p.
Keywords: Discrete mathematics; Mathematics